2023
DOI: 10.1021/acsami.2c22650
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Healing of Infected Diabetic Wounds by a Dual-Layered Adhesive Film Cored with Microsphere-Loaded Hydrogel Composite Dressing

Abstract: Diabetic wounds, a prevalent chronic disease, are associated with older age. The hyperglycemic microenvironment in diabetic wounds significantly reduces the immune system, inducing bacterial invasion. The coupling of tissue repair and antibacterial treatment is critical for infected diabetic ulcer regeneration. In this study, a dual-layered sodium alginate/carboxymethyl chitosan (SA/CMCS) adhesive film cored with an SA-bFGF microsphere-loaded small intestine submucosa (SIS) hydrogel composite dressing with a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Many studies have shown that bFGF promotes active wound repair by promoting the rapid proliferation of cells involved in wound repair, thus significantly shortening wound healing time. Moreover, prolonged release of bFGF from wound dressings has been found to enhance wound healing . Thus, we measured the functions of the nano-micro composite SAMSs on the releasing kinetics of bFGF.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that bFGF promotes active wound repair by promoting the rapid proliferation of cells involved in wound repair, thus significantly shortening wound healing time. Moreover, prolonged release of bFGF from wound dressings has been found to enhance wound healing . Thus, we measured the functions of the nano-micro composite SAMSs on the releasing kinetics of bFGF.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the SA/CMCS film provided stable adhesion to the wound, creating a moist wound environment that facilitated effective wound recovery. 279 Wang et al developed an injectable multifunctional hydrogel called FEMI hydrogel to tackle multidrug-resistant (MDR) bacterial infections in diabetic wounds. The FEMI hydrogel was formulated by incorporating EPL and MnO 2 nanosheets with a “nanoknife-like” structure.…”
Section: Application Of Hydrogel-based Dressings In Different Types O...mentioning
confidence: 99%
“…Chronic abnormal glucose metabolism in DFU patients inhibits antioxidant expression, induces excessive oxidative stress, and exacerbates wound inflammation . The high-glucose environment of the wound also provides ample nutrients for bacteria, increasing the risk of bacterial infection and impeding the resolution of inflammation . At the same time, localized hyperglycemia inhibits the proliferation and migration of fibroblasts and epithelial cells, limiting the process of cell proliferation and remodeling .…”
Section: Dfu Wound Microenvironmentmentioning
confidence: 99%